Study of the Aminoglycoside Subsistence Phenotype of Bacteria Residing in the Gut of Humans and Zoo Animals - Bello González, Teresita de J.; Zuidema, Tina; Bor, Gerrit; Smidt, Hauke; van Passel, Mark W. J. (Frontiers in Microbiology, 2016)
Recent studies indicate that next to antibiotic resistance, bacteria are able to subsist on antibiotics as a carbon source. Here we evaluated the potential of gut bacteria from healthy human volunteers and zoo animals to subsist on antibiotics. Nine gut isolates of Escherichia coli and Cellulosimicrobium spp. displayed increases in colony forming units during incubations in minimal medium with only antibiotics added, i.e. the antibiotic subsistence phenotype. Furthermore, laboratory strains of E. coli and Pseudomonas putida equipped with the aminoglycoside 3’phosphotransferase II gene also displayed the subsistence phenotype on aminoglycosides. In order to address which endogenous genes could be involved in these subsistence phenotypes, the broad-range glycosyl-hydrolase inhibiting iminosugar deoxynojirimycin (DNJ) was used. Addition of DNJ to minimal medium containing glucose showed initial growth retardation of resistant E. coli, which was rapidly recovered to normal growth. In contrast, addition of DNJ to minimal medium containing kanamycin arrested resistant E. coli growth, suggesting that glycosyl-hydrolases were involved in the subsistence phenotype. However, antibiotic degradation experiments showed no reduction in kanamycin, even though the number of colony forming units increased. Although antibiotic subsistence phenotypes are readily observed in bacterial species, and are even found in susceptible laboratory strains carrying standard resistance genes, we conclude there is a discrepancy between the observed antibiotic subsistence phenotype and actual antibiotic degradation. Based on these results we can hypothesise that aminoglycoside modifying enzymes might first inactivate the antibiotic (i.e. by acetylation of amino groups, modification of hydroxyl groups by adenylation and phosphorylation respectively, before the subsequent action of catabolic enzymes. Even though we do not dispute that antibiotics could be used as a single carbon source, our observations show that antibiotic subsistence should be carefully examined with precise degradation studies, and that its mechanistic basis remains inconclusive.